East Asian Variant of Aldehyde Dehydrogenase 2 Is Associated With Coronary Spastic Angina. Issue 19 (12th May 2015) - Mizuno, Yuji; Harada, Eisaku; Morita, Sumio; Kinoshita, Kenji; Hayashida, Mariko; Shono, Makoto; Morikawa, Yoshinobu; Murohara, Toyoaki; Nakayama, Masafumi; Yoshimura, Michihiro; Yasue, Hirofumi
<x xml:space="preserve">Abstract</x> Background— Coronary spastic angina (CSA) is a common disease among East Asians, including Japanese. The prevalence of alcohol flushing syndrome associated with deficient activity of the variant aldehyde dehydrogenase 2 (ALDH2*2) genotype is prevalent among East Asians. We examined whether CSA is associated with the ALDH2*2 genotype in Japanese. Methods and Results— The study subjects consisted of 202 patients in whom intracoronary injection of acetylcholine was performed by angiography on suspicion of CSA (119 men and 83 women; mean age, 66.2±11.4 years). They were divided into CSA (112 patients) and control groups (90 patients). ALDH2 genotyping was performed by the direct application of the TaqMan polymerase chain reaction system on dried whole blood. Clinical and laboratory data were examined using conventional methods. The frequencies of male sex, ALDH2*2 genotype carriers, alcohol flushing syndrome, tobacco smoking, and the plasma level of uric acid were higher (P<0.001, P<0.001, P<0.001, P<0.001, and P=0.007, respectively) and the plasma high-density lipoprotein cholesterol levels were lower (P<0.001) in the CSA group than in the control group. The multivariable logistic regression analysis revealed that ALDH2*2 genotype and smoking were significantly associated with CSA (P<0.001 and P=0.024, respectively). Conclusions— East Asian variant ALDH2*2 genotypes and, hence, deficient ALDH2 activity were associated with CSA in Japanese. These data support further investigation of treatment targeting aldehydes for CSA.